Current and future treatment approaches for Barth syndrome. Issue 1 (10th November 2021) - Thompson, Reid; Jefferies, John; Wang, Suya; Pu, William T.; Takemoto, Clifford; Hornby, Brittany; Heyman, Andrea; Chin, Michael T.; Vernon, Hilary J.
Abstract: Barth Syndrome is an X‐linked disorder of mitochondrial cardiolipin metabolism caused by pathogenic variants in TAFAZZIN with pleiotropic effects including cardiomyopathy, neutropenia, growth delay, and skeletal myopathy. Management requires a multidisciplinary approach to the organ‐specific manifestations including specialists from cardiology, hematology, nutrition, physical therapy, genetics, and metabolism. Currently, treatment is centered on management of specific clinical features, and is not targeted toward remediating the underlying biochemical defect. However, two clinical trials have been recently undertaken which target the mitochondrial pathology of this disease: a study to examine the effects of elamipretide, a cardiolipin targeted agent, and a study to examine the effects of bezafibrate, a peroxisome proliferator‐activated receptor (PPAR) agonist. Treatments to directly target the defective TAFAZZIN pathway are under development, including enzyme and gene therapies.